Development and Nutritional Profiling of Peanut Curd: Exploring the Impact of Microbial Inoculants on Texture, Flavour, and Functional Properties - Anupriya Kumari,; Puneet,; Gurinder Singh,; Harpreet Kaur, (International Journal of Scientific Research in Science and Technology, 2025)
The growing demand for ethical, health-conscious, and sustainable food alternatives has driven interest in plant-based products like peanut curd. This study explores the development of peanut curd using a novel inoculum comprising Lactobacillus sp., Propionibacterium acnes, natural microbiota from ginger and chili extracts, and a commercial dairy culture (Commercial curd). Each component contributed distinct metabolic activities, improving texture, flavour, and nutritional properties. Controlled fermentation revealed that Lactobacillus sp. produced a smooth-textured, tangy curd with excellent probiotic viability. Ginger microbiota added a warm, subtly spicy flavour, while chili microbiota created a bold, tangy, and spicy profile. However, P. acnes showed slower fermentation and less favourable sensory attributes, limiting its potential. Peanut curd samples were cholesterol-free and rich in proteins, carbohydrates, and fixed fats. Variants with ginger and chili demonstrated enhanced nutritional profiles, including high reducing sugar, flavonoid, and phytosterol content. Biochemical analysis revealed significant differences between peanut curds and commercial curd. Ginger and chili variants had the highest vitamin C content (85 mg/100 mL and 75 mg/100 mL, respectively) and rich metabolic diversity. Peanut curds had lower protein concentrations (0.8–1.0 mg/mL) than to commercial curd (1.2 mg/mL) but were cholesterol-free. Moisture content was slightly lower in peanut curds (80–83%) than commercial curd (84%). These results underscore peanut curd’s potential as a nutritious, lactose-free, and environmentally sustainable alternative, particularly with ginger and chili variants offering superior nutritional and functional benefits.
Keywords: Peanut curd; Plant-based products; Lactobacillus sp.; Ginger microbiota; Chili microbiota; Controlled fermentation; Probiotic viability; Nutritional properties; Cholesterol-free; Lactose-free; Sustainable food